2017
DOI: 10.1155/2017/7217619
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic Effect of Citrus aurantium L. in Crack Users

Abstract: The objective of this study was to investigate the anxiolytic effects of the essential oil (EO) of Citrus aurantium L. in patients experiencing crack withdrawal. This was developed with internal users in therapeutic communities in Paraíba, Brazil. The test population consisted of 51 volunteers, subdivided into three groups. To elicit anxiety, the Simulated Public Speaking (SPS) method was used. Physiological measures were assessed at specific phases during the experiment using appropriate equipment. Psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In another study, C. aurantium essential oils were tested in patients participating in crack cocaine withdrawal. The Analog Smoke Scale (HAS) and the Trait-State Anxiety Inventory (IDATE) were used to assess the psychological measures [66]. Results showed that patients who nebulize C. aurantium essential oils were able to maintain controlled anxiety levels during the Simulated Public Speaking (SPS) method used to evoke anxiety as compared to the control group [66].…”
Section: Anxiolytic Effectmentioning
confidence: 99%
“…In another study, C. aurantium essential oils were tested in patients participating in crack cocaine withdrawal. The Analog Smoke Scale (HAS) and the Trait-State Anxiety Inventory (IDATE) were used to assess the psychological measures [66]. Results showed that patients who nebulize C. aurantium essential oils were able to maintain controlled anxiety levels during the Simulated Public Speaking (SPS) method used to evoke anxiety as compared to the control group [66].…”
Section: Anxiolytic Effectmentioning
confidence: 99%
“…Authors' conclusions were that Citrus aurantium EO, administered by nebulization, produced anxiolytic effects in crack users in abstinence thus indicating the possibility of Citrus aurantium EO use as an alternative complementary therapy in the control of anxiety in users who are abandoning drugs abuse [56].…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies have reported that smelling or massaging essential oils such as ylang-ylang, bitter orange, and lavender could reduce HR [ 33 ], and a pleasant smell could bring a decrease in HR [ 34 ]. The BP change was observed after a few essential oil interventions such as ylang-ylang and bitter orange oil that were thought to be sedative [ 19 , 20 ]. There was no significant difference in the change of HR, BP (both diastolic and systolic blood pressure), and blood oxygen saturation between the two groups before and after the n-back training stage without odor intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, heart rate (HR) and blood pressure (BP) are often considered to be related to anxiety. In many clinical studies of essential oils, these two indicators were positively correlated with anxiety [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%